Respuesta :
The exponential equation in its generic form is:
y = A * (b) ^ t
Where,
A: initial amount
b: base (Growth rate for b> 1. Decrease rate for b <1.)
t: time.
We have then that the equation is:
N = 40.25 (1.0394) ^ t
The base is:
b = 1.0394> 1 (it is a growth rate)
Answer:
The base, b, of the exponential model is:
b = 1.0394
the base is a growth rate
y = A * (b) ^ t
Where,
A: initial amount
b: base (Growth rate for b> 1. Decrease rate for b <1.)
t: time.
We have then that the equation is:
N = 40.25 (1.0394) ^ t
The base is:
b = 1.0394> 1 (it is a growth rate)
Answer:
The base, b, of the exponential model is:
b = 1.0394
the base is a growth rate